Kemampuan Guru Dalam Melaksanakan Pembelajaran Tematik Yang Berpaikem Pada SDN INPRES 1 Tanamodindi Palu - Ertawati, Ertawati; Rede, Amram; Werdhiana, I Komang (Mitra Sains, 2015)
This study was descriptif research, to be known the teacher skills for implementing thematic learning at SDN Impres 1 Tanamodindi Palu. The data collecting by instrument: instructional observation, validity of lessons plan, observation of PAIKEM, and student’s satisfaction. The result of this study showed the skills of instructional teacher had good category (69.89%). Only two teachers had excellent category (76 and 78%). The documents of lessons plan in good category (69.14%). The teacher skills to implementing PAIKEM got a good category (68.89%), but only one teacher had a little bit good category (87.78%). The student’s satisfaction had very good category its 3.00%. Base on the study finding, it can be concluded that the sixth of teacher hope to be still improve their skills for hopefully professional teacher.